The Demographic Transition and the Sexual Division of Labor - Bruno L. S. Falc\~ao; Rodrigo R. Soares (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
This paper presents a theory where increases in female labor force participation and reductions in the gender wage-gap are generated as part of a single process of demographic transition, characterized by reductions in mortality and fertility. The paper suggests a link between changes in mortality and transformations in the role of women in society that has not been identified before in the literature. Mortality reductions affect the incentives of individuals to invest in human capital and to have children. Particularly, gains in adult longevity reduce fertility, increase investments in market human capital, increase female labor force participation, and reduce the wage differential between men and women. Child mortality reductions, though reducing fertility, do not generate this same pattern of changes. The model reconciles the increase in female labor market participation with the timing of age-specific mortality reductions observed during the demographic transition. It generates changes in fertility, labor market attachment, and the gender wage-gap as part of a single process of social transformation, triggered by reductions in mortality.
Keywords: 330; Haushaltsökonomik; Weibliche Arbeitskräfte; Lohnstruktur; Geschlecht; Demographischer Übergang; Theorie